Efektivitas Kayu Apu Dan Kangkung Air Untuk Menurunkan Kadar COD, BOD, Dan Amonia Pada Air Limbah Domestik - Anisa Imaniar; Oto Prasadi; Ilma Fadlilah (Poltekkes Kemenkes Yogyakarta, 2022)
Domestic wastewater is generated from washing clothes, kitchen and bathroom waste with high organic matter content. The purpose of this study was to determine the effectiveness of Apu (Pistia stratiotes L.) and Water Kangkung (Ipomoea aquatica F.) plants in reducing COD, BOD, and Ammonia levels in domestic wastewater at Cilacap State Polytechnic regarding the quality standard of PP RI No. 22 of 202. The acclimatization process was carried out before processing for 15 days. Wastewater treatment is carried out using 2 container boxes with a volume of 9 liters of waste water. This research was conducted using the phytoremediation method in the form of domestic wastewater with processing for 14 days. Domestic wastewater treatment at Cilacap State Polytechnic based on variations in sampling time on day 0 and day 14, it is known that the performance of Apu wood plants is better than Kangkung in reducing COD, BOD, and Ammonia levels, which are highest on day q4, which is successively to 11.3 mg/L, 3.4 mg/L, and 0.0008 mg/L. The effectiveness of reducing the concentration of COD, BOD, and Ammonia was highest on day 14 in wastewater treatment using Kayu apu plant, namely COD 60.07%; BOD 42.37%; and Ammonia 76.0%. Of the 2 plant variations used, kayu apu was more effective in reducing COD, BOD, and Ammonia.